High-Frequency Capacitor with Working Substance "Insulator-Undoped Silicon-Insulator" - N. A. Poklonski; I. I. Anikeev; S. A. Vyrko (Приборы и методы измерений)
The study of the parameters of capacitors with various working substances is of interest for the design and creation of electronic elements, in particular for the development of high-frequency phase-shifting circuits.The purpose of the work is to calculate the high-frequency capacitance of a capacitor with the working substance "insulator-undoped silicon-insulator" at different applied to the capacitor direct current (DC) voltages, measuring signal frequencies and temperatures.A model of such the capacitor is proposed, in which 30 µm thick layer of undoped (intrinsic) crystalline silicon (i-Si) is separated from each of the capacitor electrodes by 1 µm thick insulator layer (silicon dioxide).The dependences of the capacitor capacitance on the DC electrical voltage U on metal electrodes at zero frequency and at the measuring signal frequency of 1 MHz at absolute temperatures T = 300 and 400 K are calculated. It is shown that the real part of the capacitor capacitance increases monotonically, while the imaginary part is negative and non-monotonically depends on U at the temperature T = 300 K. An increase in the real part of the capacitor capacitance up to the geometric capacitance of oxide layers with increasing temperature is due to a decrease in the electrical resistance of i-Si layer. As a result, with an increase in temperature up to 400 K, the real and imaginary parts of the capacitance take constant values independent of U. The capacitance of i-Si layer with an increase in both temperature T and voltage U is shunted by the electrical conductivity of this layer. The phase shift is determined for a sinusoidal electrical signal with a frequency of 0.3, 1, 10, 30, 100, and 300 MHz applied to the capacitor at temperatures 300 and 400 K.